Environmental issue, environmental racism and covid-19: old and new challenges - Pereira Bastos, Valéria (2021)
This article is the product of the analyzes presented on the virtual table: “Environmental issue, environmental racism and COVID-19: old and new challenges”. The debate was based on theoretical contextualization regarding the environmental issue: it brought environmental epistemology, epistemicides occurred throughout history to the center of the analysis, seeking to make the analytical cut to discuss factors related to the field of political ecology and the ecologism of the poor. Empirical data referring to research carried out in Jardim Gramacho, a sub-district of the municipality of Duque de Caxias, metropolitan region of the city of Rio de Janeiro, which housed the largest dump in Latin America for three decades, was used. An attempt was made to articulate, in this territory, evidence of the expression of environmental racism, exacerbated by the Covid 19 pandemic, as a preponderant factor in the process of impoverishment of this population that, in addition to working in the area, resides there. From then on, old and new challenges were pointed out in the face of expressions of the social issue.